Schaum's outline of theory and problems of biology - Fried, George ([S.l.] : Mcgraw-Hill, 1989)
-- Over 32,000 copies sold of first edition!-- Over 709,000 students enrolled in biology courses-- Perfect supplement to the leading textbooks-- Prepares students for the MCAT-- Reflects all recent advances in quantitative biology-- Complements basic biology courses and biochemistry.
Keywords: biology,theory